Bony landmarks guided mapping of the osteophytes of the elbow osteoarthritis patients: a three dimensional computed tomograph based study - Renjie Chen; Guang Yang; Shangzhe Li; Haoyuan Deng; Hailong Zhang; Yi Lu (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteophytes in elbow osteoarthritis (OA) patients can lead to limited range of motion (ROM) and functional deficiency. However, few studies have described the osteophytes distribution and the distribution of osteophytes in elbow OA patients with different ROM and functional grades has not been studied. This study aimed to develop a classification system of elbow osteophytes based on bony landmarks to describe the location of osteophytes in patients with elbow OA, and explore whether there are differences in the incidence of osteophytes at different locations in OA patients with different elbow ROM and function scores stage. Methods 97 elbow OA patients with preoperative three dimensional computed tomograph (3D-CT) were enrolled in this retrospective study. 3D-CT of elbow joint were collected from database and the joint was divided into 11 regions, and patients were classified into three different groups according to the Qian’s ROM classification or Mayo Elbow Performance Score (MEPS) separately. The independent t-test or one-way analysis of variance was used to compare continuous variables between groups, and chi-square test was used to compare categorical variables. The intraobserver reliability and interobserver reliability of the new classification system was calculated by the Cohen kappa statistic. Results Osteophytes are most commonly found in the olecranon (93%). There were significant differences between different ROM (P < 0.001) and MEPS (P < 0.001) groups in the incidence of osteophytes in the dorsal aspect of the capitellum (region 7). Patients without osteophytes in region 7 had larger ROM (81 ± 31° vs. 65 ± 28°, P = 0.009) than those with osteophytes, and better MEPS scores (79.0 ± 15.8 vs. 69.5 ± 18.5, P = 0.007). The interobserver agreement values for the osteophytes location was 0.894 (P < 0.001); and the intraobserver agreement values for the osteophytes location was 0.908 (P < 0.001). Conclusion The bony landmarks classification system effectively delineated osteophyte distribution in elbow patients. In elbow OA patients, the olecranon is the area with the highest incidence of osteophytes. Osteophytes at the dorsal aspect of the capitellum significantly affected both elbow ROM and MEPS.